Differences in retinal microvasculature between large artery atherosclerosis and small artery disease: an optical coherence tomography angiography study - Lu, Kun; Kwapong, William Robert; Jiang, Shuai; Zhang, Xuening; Xie, Jianyang; Ye, Chen; Yan, Yuying; Cao, Le; Zhao, Yitian; Wu, Bo (Frontiers in Aging Neuroscience, 2022)
Purpose: Recent reports suggest retinal microvasculature mirror cerebral microcirculation. Using optical coherence tomography angiography (OCTA), we investigated the retinal microvasculature differences between ischemic stroke patients with large artery atherosclerosis (LAA) and small artery disease (SAD). Methods: All patients underwent MR imaging and were classified as SAD and LAA; LAA was subdivided into anterior LAS and posterior LAS depending on the location. Swept-source OCTA (SS-OCTA) was used to image and segment the retina into the superficial vascular complex (SVC) and deep vascular complex (DVC) in a 6 × 6 mm area around the fovea. A deep learning algorithm was used to assess the vessel area density (VAD, %) in the retinal microvasculature. Results: Fifty-eight (mean age = 60.26 ± 10.88 years; 81.03 % males) were LAA while 64 (mean age = 55.58 ± 10.34 years; 85.94 % males) were SAD. LAS patients had significantly reduced VAD in the DVC (P = 0.022) compared to SAD patients; the VAD in the SVC did not show any significant difference between the two groups (P = 0.580). Anterior LAA ischemic stroke showed significantly lower VAD (P = 0.002) in the SVC compared with posterior LAS patients. There was no significant difference in the DVC between the two groups (P = 0.376). Conclusions: We found LAA patients had significantly reduced DVC density compared with SAD; we also showed anterior LAA patients had significantly reduced SVC density compared with posterior LAA. These findings suggest retinal imaging has the potential to be used to detect microvasculature changes in subtypes of ischemic stroke.